Evaluación de fungicidas de un mismo grupo químico con diferentes ingredientes activos en el control de Sigatoka negra (Mycosphaerella fijiensis) en el cultivo de banano - Echeverria Anchundia, Dany Fernando (2021)
Ecuador is one of the main banana producers in the world, which makes the country a power in terms of the cultivation of this fruit, as all agricultural crops are affected by diseases caused by pathogenic fungi such as Black Sigatoka (Mycosphaerella fijiensis) which is very common to be able to appreciate them, but if it is not treated with judgment and caution, it can damage all banana production, leading to an economic crisis for the producers. The present investigation studied the effect of different chemical fungicides to achieve control of M. fijiensis; three of the treatments had different formulations belonging to various chemical groups such as: Carboxamide, Amines, Strobilurins and Triazoles, a control treatment (Oil) was used. Determining that in week 05, in the efficiency variables such as total leaves and leaves free of burning, if there were statistical differences between the treatments (p <0.05), the variable leaves free of streaks and leaf emission did not report statistical difference (p> 0.05) between the treatments, showing that with the course of the disease the management of different chemical groups offers greater health. When studying the residuality of the chemical groups made up of different molecules, highly significant statistical differences were reported (p <0.05). T1 (Boscalid + Fennpropimortf + Pyraclostrobin + Epoxiconazole) obtained the least affected leaf area in all the days evaluated. The lowest cost of treatments was registered in the control treatment followed by treatment T2 (Izopyrazam + Fenpropidin + Azoxystrobin + Difenoconazole) and T1 Boscalid + Fennpropimortf + Pyraclostrobin + Epoxiconazole) with values of $ 227.52 and $ 247.42. Key words: Black leaf streak, banana, disease, cover, pathogen.